Short Communication Immunization coverage of health care workers against hepatitis B - Mostafa, Naderi; Faizi, Fakhraddin; Tajic, Jamshid (Archives of Medical Science, 2006)
Introduction: Hepatitis B virus (HBV) infection remains a serious risk for health care workers (HCWs). Vaccination of the group against HBV therefore is a central part of programs to prevent nosocomial infections in healthcare workers. An evaluation of the anti-HBs level in vaccinated persons is a necessary measurement to handle immunization coverage. Material and methods: We evaluated the Anti-HBs level of 100 randomly selected HCWs in an Educational Hospital 6 months after implementing a vaccination program against HBV to handle the immunization coverage of HBV in the group. Results: 90 (90%) HCWs responded to the immunization program that 72 (72.0%) had anti-HBs titers in an equal range (>10 MIu/L), 18 (18%) were <10 MIU/L and 10 had negative anti-HBs. Conclusions: Immunization coverage should be assessed to find out low-responded or non-responded healthcare workers to immunization. Some factors such as age, gender, race and storage conditions of vaccine may interfere with one’s response to immunization.